Weekly programming of hamstring-related training contents in European professional soccer - Gómez-Piqueras, P.; Martínez-Serrano, A.; Freitas, T. T.; Díaz, A. G.; Loturco, I.; Giménez, E.; Brito, J.; García-López, D.; Giuria, H.; Granero-Gil, P.; Huygaerts, S.; Cos, F.; et al. (Sports, 2024)
Hamstring injuries in soccer continue to be a challenge for professionals who work with soccer players daily. Although its origin is multifactorial, the proper management of neuromuscular fatigue during the training microcycle is a very important factor to consider. There are no clear guidelines regarding the weekly distribution of certain exercises that demand the hamstrings. The main objective of this study was to describe the usual training practices of professional European soccer teams. An international observational survey design was applied to some of the strength and conditioning coaches of professional soccer teams. The survey included different neuromuscular demanding exercises for the hamstrings. For each exercise, the strength and conditioning coaches had to respond in relation to their frequency of use and timepoint depending on the day of the weekly microcycle. Although there is no strong consensus in this regard, there does seem to be a trend when applying certain exercises, especially on the days matchday-4 and matchday-3.